Optimizing the Use of Social Crowdfunding in SMEs to Encourage the Implementation of Circular Economy (CE) Practices - Mohamad Nasoha; Hubertina Karolina Ngarbingan; Ginta Ginting; Maya Maria; Zulfahmi Zulfahmi (International Journal of Applied Business and International Management, 2024)
Circular Economy (CE) offers an alternative to the linear economy (take-make-dispose) by adopting a make-use-recycle approach. While CE practices have primarily focused on technological and manufacturing changes, large businesses can more easily implement these practices due to their resources. However, small and medium-sized enterprises (SMEs) often struggle with CE implementation due to limited resources, particularly funding. FinTech Crowdfunding, especially donation-based (social crowdfunding), presents a viable funding alternative for SMEs. This research aims to develop a theoretical model using the Willingness to Participate Theory and the AIDA model for understanding and promoting CE practices among SMEs through the use of social crowdfunding. A survey was conducted with 69 SME actors. The research findings have led to the development of a model incorporating three key determinants: funding resources, community engagement, and entrepreneurial spirit. These factors are identified as antecedents that significantly influence SME awareness and willingness to adopt CE practices. The proposed model highlights how these elements can enhance SME participation in Indonesia. This model can serve as a foundation for future research in this area.